(untitled) (KYAMC Journal, 2017)
We report a 70 years old postmenopausal lady Mrs Johura Begum presented to us with the complaints of watery and foul smelling per vaginal discharge for 4-5 months, occasional per vaginal bleeding for 2-3 months lower abdominal pain for 15 days, fever for 7 days. On general examination she was restless, her temperature was 1020F and lower abdomen was tender. On per vaginal examination there were foul smelling discharge and a large ulcerated and necrossed mass in the vaginal canal that bleeds on touch. She was managed surgically. Now she is on chemotherapy and well. KYAMC Journal Vol. 7, No.-2, Jan 2017, Page 818-820